Analisa Peran Kepala Madrasah Dalam Meningkatkan Manajemen Mutu Pendidikan Dan Kinerja Guru Di MTS Se-Rantau Kampar Kiri - Putra Tama, M. Sahlan (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This study aims to determine the role of principal, what are the supporting and inhibiting factors of the principal's role in improving education quality management and teacher performance at MTs Se-Rantau Kampar Kiri. Includes a type of field research with a qualitative and phenomenological method approach. Data collection is obtained using observation, interview, documentation, and is complemented by validity testing. The data analysis technique uses procedures that include data collection, data reduction, data presentation, drawing conclusions and verification. The results of study found that the role of principal in improving education quality management and teacher performance includes; (1) Arranging curriculum planning that will be taught by teachers; (2) Organizing students' learning experiences; (3) Organizing students' skills well in religious studies; (4) Promoting madrasah libraries; (5) Strengthening students' interest in reading; (6) Strengthening student achievement in all fields; (7) Assigning teachers according to their expertise; (8) Paying attention to the development of students taught by these teachers; (9) Supervising the teacher who teaches once a week; (10) Increasing work commitment with teachers in learning; (11) Empowering all elements of the madrasah to improve learning achievement; (12) Providing pre-facilities to support education; (13) Conducting evaluation meetings once a month; (14) Making decisions based on agreement with the teachers' council; (15) Establishing communication with all components to improve student learning achievement. Then the factors that support the role of principal are; (1) Communication; (2) Freedom; (3) Work experience, while the inhibiting factors can be said to be non-existent, because all of these factors can be addressed by the principals of MTs in Rantau Kampar Kiri